Managing Burning Mouth Syndrome with Omega-3 Fatty Acids: A Clinical Trial of Pain Relief and Quality of Life Improvement - Rahul Srivastava; Saquib Khan; Dhirendra Kumar Singh; Sangita Nath; Dharitri Bharali; Hiroj Bagde (Journal of Pharmacy and Bioallied Sciences)
Introduction: An inexplicable burning sensation in the oral mucosa is the hallmark of Burning Mouth Syndrome (BMS), a chronic illness that is often connected to inflammatory and neuropathic processes. Materials and Methods: A double-blind, randomized, placebo-controlled study including 120 individuals with a BMS diagnosis was carried out. Over the course of 12 weeks, participants were randomized to receive either a placebo or 2 grams of omega-3 fatty acids (EPA and DHA) daily. The Visual Analog Scale (VAS) was used to quantify the change in pain intensity, which was the main result. Secondary outcomes were patient-reported symptom alleviation and quality of life as measured by the Oral Health Impact Profile (OHIP-14). Results: In total, 110 out of the 120 individuals finished the study. When compared to the placebo group, the omega-3 group’s VAS pain ratings significantly decreased (mean change: -3.4 vs. -1.2, P < 0.001). Additionally, the omega-3 group saw considerably higher improvements in quality of life, with a mean decrease in OHIP-14 ratings of -8.7 points compared to -3.1 in the placebo group (P < 0.001). In the omega-3 group, most patients experienced moderate to total symptom alleviation (82% vs. 45%, P < 0.001). The omega-3 group had higher gastrointestinal pain, although adverse effects were generally moderate. Conclusion: Omega-3 fatty acid supplementation significantly reduces pain and improves quality of life in patients with BMS, providing a safe and effective alternative to conventional treatments.